Isolation and characterisation of a culm-specific promoter element from sugarcane - Goshu Abraha, Tsion (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MSc (Botany and Zoology. Plant Biotechnology))--University of Stellenbosch, 2005.